Application of Obligatory Prayer Learning Based on Augmented Reality - Rahmawati Febriyaning Tias; M. Mahaputra Hidayat; Eko Prasetyo; Ari Tria Widagda; Anis Suryaningrum (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
Prayer is a physical, mental, and spiritual activity that gives good meaning to relationships with Allah, fellow human beings, and oneself. Prayer begins with ablution first to remove najis and hadats. Religion is a rule, guideline, teaching, or system that governs beliefs, beliefs, or beliefs. Islam was revealed by Allah SWT. In Islam, expressing gratitude for every Muslim to the Creator is by praying. Moreover, at this time, the current guidance book on prayer procedures is still running in the delivery of information in the form of text and 2D images. This way is not valuable because it is not mobile style, while currently, human mobility is higher. In this study, we are designing and building a learning application of obligatory prayer based on augmented reality to run on Android-based smartphones and can be studied anywhere and anytime without being limited by space and time. This application contains procedures for ablution and movements of people praying in the form of 3D animation and audio.